PENGETAHUAN KESEHATAN KESELAMATAN KERJA (K3) MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK OTOMOTIF FAKULTAS TEKNIK UNIVERSITAS NEGERI YOGYAKARTA TERHADAP BAHAYA KECELAKAAN DI BENGKEL LAS - Yusfiq Harvana (Jurnal Pendidikan Vokasi Otomotif, 2021)
This study aims to determine the awareness of Occupational Health and Safety (OHS) of students of the automotive engineering education study program at the UNY Faculty of Engineering against the danger of accidents in the welding workshop, which includes attitude knowledge (discipline and awareness), environmental knowledge (workshop state), equipment knowledge (equipment usage and maintenance), and health inspection knowledge.This research is a quantitative descriptive. The subjects of this study were the students of the Mechanical Engineering Education Study Program of UNY, and the research instruments consisted of 60 students. Research data collection was done by using questionnaires. The test instrument is based on the validity test with the product moment correlation formula, while the reliability test is based on the Spearman-Brown formula. The results of data analysis are presented in the form of achievement scores and then elaborated.Occupational Health Safety Knowledge (OHS) students of the automotive engineering education study program at the UNY faculty of engineering against accidents in the welding workshop, carried out with 6 knowledge measuring variables, namely: 1) students’ knowledge on attitude (discipline) meets the criteria very well, with an achievement score of 81% , 2) students’ knowledge on attitude (awareness) has good criteria, with an achievement score of 73%, 3) students’ knowledge on the environment (workshop state) has good criteria, with a score of 73%, 4) student knowledge on equipment (use of equipment) has good criteria, with a score of 73%, and 5) student knowledge on equipment (equipment maintenance) has good criteria, with a score of 71%, 6) student knowledge on health examination has very good criteria, with a score of 83%. Overall Occupational Health Safety Knowledge (K3) Students of the automotive engineering education study program at the UNY Faculty of Engineering against the dangers of accidents in the welding workshop have good achievement criteria, with an achievement score of 75%